A Comparative Study of Effects of Adding Dexmedetomidine and Fentanyl as an Adjuvant to Isobaric Levobupivacaine in Lower Segment Cesarean Section: A Prospective Randomized Double-Blind Clinical Study - Bharti, Alok Kumar (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Background: The most often used local anaesthetic for lower segment caesarean section is intrathecal Bupivacaine, although researchers are constantly looking for new local anaesthetics with superior safety profiles for both the mother and the foetus. Many adjuvants have been used with intrathecal local anaesthetics in the past to prolong intraoperative anaesthesia and postoperative analgesia, such as fentanyl, morphine, or tramadol. The use of dexmedetomidine as an adjuvant with isobaric levobupivacaine is not documented in the literature. As a result, we aimed to compare dexmedetomidine and fentanyl in spinal anaesthesia for lower segment caesarean sections when combined with 0.5 percent isobaric intrathecal levobupivacaine. Methodology: Patients were allocated into three equal groups after institutional ethical committee approval and informed written consent: Group L; to receive 2.5ml of 0.5% of isobaric levobupivacaine intrathecally; Group LD to receive 2.5 ml of 0.5% of isobaric levobupivacaine and 5 µg dexmedetomidine intrathecally and Group LF to receive 2.5 ml of 0.5% of isobaric levobupivacaine and 25µg fentanyl intrathecally. The length of sensory and motor blockade from the time medicines were delivered intrathecally was the primary endpoint. A chi-square test or Fischer's exact test, as well as One-way ANOVA or Kruskal Wallis test, were used for statistical analysis. Statistical significance was defined as a P value of less than 0.05. Results: The duration of sensory and motor blockade in the LD group was substantially longer (P<0.001) than in the LF or L groups. The LF group experienced sensory and motor blockade earlier than the LD and L groups (P < 0.001).The LD group had a longer time to initial rescue analgesia than the LF and L groups (P <0.001). Conclusion: When used as adjuvants to 0.5 percent isobaric levobupivacaine in elective caesarean section, intrathecal dexmedetomidine produced longer blockade and postoperative analgesia than fentanyl.